Perlindungan Hukum Bagi Anak Korban Tindak Pidana - Airi Safrijal; Rizki Amanda (Fakultas Hukum Universitas Muhammadiyah Aceh, 2018)
Article 15 letter f of Law Number 35 of 2014 on Child Protection states that every child has the right to get protection against sexual crimes. Legal protection for child victims of sexual crimes has been given but not fully due to lack of information and economic factors, The form of protection provided for child sexual victims is, (1) separating children from the defendant at trial, (2) names of children are obscured, (3) recovery child trauma, and (4) medical needs are sought if needed.